16.0k views
3 votes
PLEASE HELP 20 POINTS




.5(4x - 2) - 2(3x + 3) = 9 + 2(x+ 4)

User Annalee
by
5.5k points

1 Answer

5 votes

Answer:


x = -4

Explanation:

To solve this equation, we need to apply the distributive property, combine like terms, and get x on one side of the equation.

First, let's apply the distributive property to all parts of the equation:


0.5(4x-2) - 2(3x+3) = 9+2x + 8


2x - 1 - 6x - 6 = 9 + 2x + 8

Combine like terms:


-4x - 7 = 2x + 17

Add 4x to both sides:


-7 = 6x + 17

Add -7 to both sides:


0 = 6x + 24

Subtract 24 from both sides:


6x = -24

Divide both sides by 6:


x = -4

Hope this helped!

User Bruna
by
5.0k points